IOS, Company Growth, and Profitability to Firm Value Moderated By Dividend Policy - Hulaila, Aini; Ika Prajawati, Maretha (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to quantify how IOS, growth, and profitability affect firm value while taking dividend policy into account as a moderator. Firm value is regarded as a crucial metric that shows how well a business can generate value for its investors. There are 27 samples of financial sector companies that have distributed dividends and are listed on IDX for 2020-2023 periods as samples. Data analysis using panel data linear regression and MRA methods through SPSS version 27 shows IOS correlates positively to firm value, while growth and profitability are not significant. Dividend policy is found to moderate the relationship between firm growth and firm value, but not IOS and profitability. This study will contribute an empirical study in financial literature and have implications for investors, corporate management, and capital market regulators.